If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-3w) = -10 + -4w Solving (-3w) = -10 + -4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '4w' to each side of the equation. (-3w) + 4w = -10 + -4w + 4w Combine like terms: (-3w) + 4w = 1w 1w = -10 + -4w + 4w Combine like terms: -4w + 4w = 0 1w = -10 + 0 1w = -10 Divide each side by '1'. w = -10 Simplifying w = -10
| 3x-32=-7x+5 | | 2x-8=-32 | | 5x^3+6x^2=0 | | (-5-6i)(7+8i)= | | 30u+4=10 | | b-9=4b | | g=3x-(2+x)(4x-3) | | 497*x=-20 | | 7(2x+14)=210 | | 3x+6=2(3x+12) | | -5+2a=3a+2 | | 42-4y=3y | | 64+4y=3y | | 5(2.95-a)=47.75 | | -(x-8)=2(x-6)+10 | | 140+10x=20+12x+x^2 | | 64+7u=15u | | (-2x+9)=0 | | 3(j+5)=(11-j) | | 9x^4+3x^3=0 | | 7x+499= | | (.5x-5)=0 | | 3u=28-u | | 2ab+4c= | | (N)=3-2n | | 5[6-(-2x-6)]=54x+126 | | 12x+6x-14=20 | | (4u)=(5)+u | | (3d+4)=0 | | 4=2+4x | | 5(1.5-w)=71.25 | | 24=4-2n |